Three-Phase Series Resonant DC-DC Boost Converter with Double LLC Resonant Tanks and Variable Frequency Control - Salem M.; Ramachandaramurthy V.K.; Jusoh A.; Padmanaban S.; Kamarol M.; Teh J.; Ishak D. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric inverters; MATLAB; Natural frequencies; Switching frequency; Zero voltage switching; Converter performance; DC-DC boost converters; LLC resonant converter; Operating frequency; Series resonant converters; Three-phase inverter; Variable frequency control; Variable frequency controllers; DC-DC converters